Sustaining the growth of SME beach resorts: a case study of Perhentian Island - Awang, Khairil Wahidin; Mustapha, Mazlina (Penerbit Universiti Malaysia Terengganu, 2020)
Coral reefs are proved to be valuable resources for resorts and ecotourism operators. This study seeks to understand on how SME typed beach resorts grow in amid of challenges at Perhentian, a famous island destination of Malaysia. SMEs are vital cog in Malaysia’s realization to become a developed nation. SMEs in tourism-related industry contribute towards fulfilling future targets of tourist arrivals and expenditures. Similarly, resort, a form of the accommodation sector, plays a significant role in accommodating increase number of tourist arrivals. The authors employed in-depth interview technique on two resorts to gather primary data. Findings indicate that these resorts faced many challenges even though typically SMEs possess low entry level. Challenges range from difficulties in accessing capital, higher operation costs of resourcing utilities like electricity and water to facing external threats like seasonal monsoon and the lack of infrastructure provisions. The outcome of this research would be beneficial to other SME players specifically owners or managers of such resorts and policy makers from the Ministry of Tourism and Culture of Malaysia. Policy makers could further streamline their policies to better facilitate the channelling of loans or funds to potential and new players, stimulating further the SME’s arena.